PERSEPSI MAHASISWA PPKN ANGKATAN 2022 TERHADAP TANTANGAN KOMUNIKASI ANTARBUDAYA DI UNIVERSITAS NEGERI MALANG - Aprilia Dewi, Tisa (Social Sciences Journal, 2025)
This research is a descriptive quantitative study aimed at understanding the perceptions of PPKn students from the 2022 cohort regarding intercultural communication challenges at State University of Malang. The sample used in this study consists of 58 students from the 2022 PPKn cohort, selected using the simple probability sampling method. Data collection used primary data sources in the form of questionnaires that have been tested for validity and reliability. The measurement scale used is the Likert scale. The data obtained were then analyzed descriptively using the percentage formula. The results of this study on the perceptions of PPKn students regarding intercultural communication challenges consist of 5 aspects: physical environment (43.10%), lack of experience (46.55%), emotional challenges (43.1%) related to calmness and openness, which reflect an emotional level that is still fluctuating, non-verbal challenges (51.72%) related to difficulties in understanding facial expressions and body language, and competition (43.1%) in doing two activities simultaneously, which can lead to ineffective intercultural communication.